2006
DOI: 10.1063/1.2363169
|View full text |Cite
|
Sign up to set email alerts
|

Interband cascade laser operating cw to 257K at λ=3.7μm

Abstract: A five-stage interband cascade laser with 12μm ridge width and Au electroplating for improved epitaxial-side-up heat sinking operates cw to a maximum temperature of 257K, where the emission wavelength is 3.7μm. The device emits 100mW̸facet for cw operation at 80K, 54mW at 200K, and 10mW at 250K. The beam quality is within twice the diffraction limit for injection currents up to 14 times the lasing threshold at 120K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Type-II devices progressed more quickly due to the reduced Auger recombination rates stemming from the spatial separation of electrons and holes in the staggered type-II band alignments [46]. ICLs lend themselves well to cascaded designs, much like QCLs, the difference being that the optical transitions occur band-to-band [40], [47], [48]. The development of these devices has been rapid.…”
Section: Highly Strained Mid-infrared Type-i Diode Lasers On Gasbmentioning
confidence: 97%
“…Type-II devices progressed more quickly due to the reduced Auger recombination rates stemming from the spatial separation of electrons and holes in the staggered type-II band alignments [46]. ICLs lend themselves well to cascaded designs, much like QCLs, the difference being that the optical transitions occur band-to-band [40], [47], [48]. The development of these devices has been rapid.…”
Section: Highly Strained Mid-infrared Type-i Diode Lasers On Gasbmentioning
confidence: 97%
“…4͒ and lattice matched InGaAs/ AlAsSb, 5 only one QCL operating continuous wave ͑cw͒ at room temperature and at wavelengths below 4.0 m has been reported. 6 The longest wavelength for room temperature cw operation for a type I interband diode is ϳ3.1 m, 7 whereas maximum cw operating temperatures of 264, 8 257, 9 and finally 269 K, 10 at emission wavelengths of 3.3, 3.7, and 4.05 m, respectively, have been achieved recently by interband cascade lasers ͑ICLs͒, which have also achieved cw power outputs above 1 W at 78 K. 11 The aluminum-indium-gallium-antimonide ͑Al x Ga y In 1−x−y Sb͒ material system offers great promise for efficient diode laser operation across the 3 -5 m wavelength range. It offers an excellent compromise between the requirements for good electronic and optical confinement and those for low series resistance, and the use of an active region comprising compressively strained type I quantum wells is predicted to lead to increased gain, which leads to lower threshold current densities and hence reduced nonradiative Auger recombination.…”
mentioning
confidence: 99%
“…The range 2500-nm to 4500-nm is more challenging (as discussed later), and is currently the subject of intense research, with sources demonstrated only under cryogenic conditions to date [14]. A helpful recent review of semiconductor sources in the range > 1500-nm is given by [15].…”
Section: Wavelength Of Absorption Tinesmentioning
confidence: 99%
“…Figure 8 also shows an estimate of the lower possible lasing wavelength of these quantum cascade laserswhich is at approximately 4000-nm. There is currently no semiconductor laser design or material which can deliver high performance at room temperature in this intermediate wavelength range of 2500-nm to 4000-nm, although there are designs that operate well at cryogenic temperatures [14]. …”
mentioning
confidence: 99%